Serum leptin and homeostasis model assessment-IR as novel predictors of early liver fibrosis in chronic hepatitis B virus infection. Issue 4 (2nd October 2018) - Mousa, N; Abdel-Razik, A; Sheta, T; Shabana, W; Zakaria, S; Awad, M; Abd Elsalam, M; El-Wakeel, N; Elkashef, W; Effat, N; Elgamal, A; Deiab, AG; et al.
ABSTRACT: Background : The relationship between hepatitis B virus (HBV) infection, leptin and insulin resistance remains unclear. We hypothesised links between serum leptin and insulin resistance in non-diabetic patients with chronic viral hepatitis B infection and their relation to liver fibrosis. Methods : We recruited 190 untreated patients with chronic HBV infection and 72 healthy controls. Serum leptin, fasting glucose, insulin, liver function tests (LFTs), C-peptide and Homeostasis model assessment-IR (HOMA-IR) were measured/calculated by ELISA and standard techniques. Results : Serum leptin, C-peptide (both P < 0.001), HOMA-IR ( P = 0.021) and several LFTs were increased in patients with chronic HBV-infection. In multivariate regression analysis, both HOMA-IR ( P = 0.003) and leptin ( P = 0.002) were significant independent predictors of HBV infection. There were significant positive correlations ( P < 0.01) between leptin and HOMA-IR ( r = 0.81), between serum leptin and METAVIR activity ( r = 0.95), and between HOMA-IR and BMI ( r = 0.75), fasting glucose ( r = 0.005), and fasting insulin ( r = 0.81). Several LFTs, glucose and insulin correlated modestly ( r = 0.61–0.69, P < 0.05) with leptin. Conclusion : Serum leptin may be related to the rate of fibrosis progression in nondiabetic patients with chronic HBV infection. Follow-up by serial measurement of serum leptin and HOMA-IR in non diabetic HBV-infected patients may be used as a non-invasive marker of early liver fibrosis.